Antimicrobial Activity of Root Canal Filling Materials - Liubchenko , Olga; Velihoria, Iryna; Poliakova , Svetlana; Pushkar , Liudmil; Nikonova , Anna; Vashakidze , Nazi (Caucasus Journal of Health Sciences and Public Health, 2020)
The antimicrobial activity of filling materials was studied to improve the quality of treatment of complicated caries in vitro. Resorcin-formalin cement Resodont (“Latus”, Ukraine) - № 1; Endocort zinc oxide-eugenol cement (“Latus”, Ukraine) - No. 2; materials based on zinc oxide eugenol cement with dexamethasone: Endomethasone ivory (Septodont, France) - No. 3 and Endofil (“ProduitDentaires SA”, Switzerland) - No. 4. To assess the antimicrobial activity of the studied materials, test microorganism strains were used: Staphylococcus aureus ATCC 25923, Enterococcus faecalis ATCC 6783, Candida albicans ATCC 885-653. As a result of the study, it was established that filling materials have different antimicrobial activity. Resodont has the greatest antimicrobial activity on the test culture. Endomethason is active in relation to the test cultures studied, inferior to Resodont in its antimicrobial properties. Endocort and Endofil have less antimicrobial activity than Resodont and Endomethason, but have approximately equal growth retardation rates. It should be noted that with respect to Staphylococcus aureus, Endocort was found to be almost 1.5 times more active than Endofil. The conducted studies confirm that the materials for filling of root canals by Resodont and Endocort (Latus, Ukraine) have a pronounced antibacterial effect. They are competitive with foreign sealers and are the materials of choice, having a significantly lower cost.